2020
DOI: 10.1186/s12933-020-01132-2
|View full text |Cite|
|
Sign up to set email alerts
|

Combination therapy with pemafibrate (K-877) and pitavastatin improves vascular endothelial dysfunction in dahl/salt-sensitive rats fed a high-salt and high-fat diet

Abstract: Background Statins suppress the progression of atherosclerosis by reducing low-density lipoprotein (LDL) cholesterol levels. Pemafibrate (K-877), a novel selective peroxisome proliferator-activated receptor α modulator, is expected to reduce residual risk factors including high triglycerides (TGs) and low high-density lipoprotein (HDL) cholesterol during statin treatment. However, it is not known if statin therapy with add-on pemafibrate improves the progression of atherosclerosis. The aim of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The protective effects of PEM have been documented in extrahepatic organs both in mouse experiments and in the clinical setting. For example, PEM promoted ischemia-induced revascularization through eNOS-dependent mechanisms in mice [ 35 , 36 ]. PEM also attenuated neointima formation after vascular injury in mice fed normal chow and a high-fat diet [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effects of PEM have been documented in extrahepatic organs both in mouse experiments and in the clinical setting. For example, PEM promoted ischemia-induced revascularization through eNOS-dependent mechanisms in mice [ 35 , 36 ]. PEM also attenuated neointima formation after vascular injury in mice fed normal chow and a high-fat diet [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PEM promoted ischemia-induced revascularization through eNOS-dependent mechanisms in mice [ 35 , 36 ]. PEM also attenuated neointima formation after vascular injury in mice fed normal chow and a high-fat diet [ 36 , 37 , 38 ]. However, according to the results of the current study, those favorable PEM effects may not have been caused by the direct activation of PPARα in extrahepatic tissues, such as the endothelium and vascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic blood pressure and pulse rate were measured at 0, 11 and 18 days using tail-cuff plethysmography (MK-2000, Muromachi, Tokyo, Japan) 41 . An average of three measurements was used.…”
Section: Methodsmentioning
confidence: 99%
“…Honda et al revealed that pemafibrate attenuated hepatic triglyceride contents, macrophage infiltration, and hepatic fibrosis in a diet-induced steatohepatitis model 19 . Yoshida et al also reported that pemafibrate and statins improved vascular endothelial dysfunction in dahl/salt-sensitive rats 20 . Although a previous report indicated that another fibrate, fenofibrate, had a protective role against cardiac injury in a porcine myosin-induced rat myocarditis model 21 , no study has investigated whether pemafibrate might regulate cardiac inflammation or cholesterol metabolism in the heart.…”
Section: Introductionmentioning
confidence: 93%